Lycopene Exerts Neuroprotective Effects After Hypoxic–Ischemic Brain Injury in Neonatal Rats via the Nuclear Factor Erythroid-2 Related Factor 2/Nuclear Factor-κ-Gene Binding Pathway - Fu, Changchang; Zheng, Yihui; Zhu, Jinjin; Chen, Binwen; Lin, Wei; Lin, Kun; Zhu, Jianghu; Chen, Shangqin; Li, Peijun; Fu, Xiaoqin; Lin, Zhenlang (Frontiers in Pharmacology, 2020)
Neonatal hypoxic-ischemic encephalopathy (HIE) is a brain injury caused by perinatal asphyxia and is the main cause of neonatal death and chronic neurological diseases. Protection of neuron after hypoxic-ischemic (HI) brain injury is considered as a potential therapeutic target of HI brain injury. To date, there are no effective medicines for neonatal HI brain injury. Lycopene (Lyc), a member of the carotenoids family, has been reported to have anti-oxidative and anti-inflammatory effects. However, its effects and potential mechanisms in HI brain injury have not yet to be systematically evaluated. In this study, we investigated whether Lyc could ameliorate HI brain injury and explored the associated mechanism both in vivo and in vitro experiments. In vivo study, Lyc significantly reduced infarct volume and ameliorated cerebral edema, decreased inflammatory response, promoted the recovery of tissue structure, and improved prognosis following HI brain injury. In vitro study, results showed that Lyc reduced expression of apoptosis mediators in oxygen-glucose deprivation (OGD)-induced primary cortical neurons. Mechanistically, we found that Lyc-induced Nrf2/NF-κB pathway could partially reversed by Brusatol (an Nrf2 inhibitor), indicated that the Nrf2/NF-κB pathway was involved in the therapy of Lyc. In summary, our findings indicate that Lyc can attenuated HI brain injury in vivo and OGD-induced apoptosis of primary cortical neurons in vitro through the Nrf2/NF-κB signaling pathway.